The Impact of Screen Time on Eye Health: Clinical Implications and Prevention: A Literature Review - Praksosa, I Made Andika Prakosa; Prajnaparamita, Irfani (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
The increased use of digital devices has led to a surge in screen time, significantly impactingeye health. The effects include computer vision syndrome, digital eye strain, and a rise inmyopia, particularly among children.Objective: This article aims to evaluate the impact ofscreen time on eye health, identify the underlying mechanisms, and summarize effectiveprevention strategies.Methods: A literature review was conducted on scholarly articlespublished since 2020, using databases such as PubMed, Scopus, and Google Scholar. Thesearch focused on epidemiological studies, physiological mechanisms, and mitigation effortsrelated to screen time.Results: Studies indicate that increased screen time is associated with arise in eye complaints, such as dry eyes, visual fatigue, and accommodation disorders. Riskfactors include blue light exposure, improper viewing distances, and prolonged device usage.Prevention measures such as the 20-20-20 rule, blue light filters, and ergonomic workplaceadjustments have proven effective in reducing symptoms.Conclusion: Excessive screen timenegatively affects eye health, particularly among the younger population and office workers.Public education and the implementation of preventive strategies are needed to minimize thisimpact.